The Effect Of Employee Engagement on Employee Performance at PT. Citra Lampia Mandiri Luwu Timur District - Riyanti; Bakhtiar; Muh Rizal S (Public Resource Innovation Management and Excellence, 2024)
This study aims to determine the Effect of Employee Engagement on Employee Performance at PT. Image of Lampia Mandiri East Luwu Districk.This study used a quantifiable approach method of descriptive research type with a population of 51 respondents and a sample in this study of 51. Data collection techniques used through observation, questionnaires (questionnaires), and documentation. The data obtained from the results of the study were processed using data analysis and using the SPSS 25 software application which consists of descriptive analysis techniques and inferential statistical analysis. The results showed that the indicators on each variable used, where the employee attachment variable showed that the indicators used in this study were in the very good category (81.96). As for the indicators on the employee performance variables, they show in the excellent category (80.10). The results of the determinant coefficient (r2) test obtained by 0.858 or 85.8% of employee performance are influenced by employee attachment. So it can be concluded that there is a significant influence between employee attachment to employee performance at PT. Image of Lampia Mandiri East Luwu Districk.